Představuje Re-exposure Draft: Leases cestu ke splnění záměrů IASB a FASB? - Svoboda, Patrik; Bohušová, Hana (Vysoké učení technické v Brně, Fakulta podnikatelská, 2014)
Purpose of the article: The issue of leases includes the controversial areas in the IFRS and US GAAP convergence efforts. Especially the current principles applied to the recording and reporting of operating lease with a relatively longer period of lease are a subject of criticism. The development of methodological approaches for lease reporting especially on the side of lessee that would eliminate the main weaknesses of the current system of reporting based on the classification of lease contracts in connection with the lease term and the transfer of risks and benefits associated with the lease to the lessee should be the result of the convergence activities in this area. The evaluation of the impact of the newly proposed methodological approaches to lease reporting in the field of operating leases into the financial statements of lessee that will be affected by this change of methodology. Methodology/methods: The standard scientific methods were used to fulfill the defined aim. Analysis, synthesis and comparison were used in the theoretical part of the research. There was used a sample of lease contracts with various parameters (lease term in connection to useful life of leased asset, interest rate, options to extend the contract.). Based on the above mentioned sample, the impact into financial statements and selected indicators of financial analysis with a focus on indicators, in whose construction are used items of statements that are significantly affected by the change of the methodological approach is evaluated as well. Findings: Application of new methodologies leads to changes in values of selected items of financial statements (financial position statement and profit and loss statement). The paper focuses on the lease contracts, which, according to the existing methodology, are mostly classified as operating lease and according to the proposed methodology would be recognized as a lease type A or B. Conclusions: The proposed standard helps to a more faithful representation of leased asset. Classification of leases of the type A and B allows to take into account the differing nature of lease contracts. Classification of lease as type B can cause overvaluation of total assets arising from the lease contract. Other possible asymmetry cannot be excluded, for example such cases, when the lessor classifies lease as type B and lessee as type A.
Is the Re-exposure Draft: Leases the Right Way to Fulfill the IASB and FASB Goals in this Area?
Keywords: convergence; financial lease; operational lease; right to use; derecogniton